Alluring Indonesian Culinary to Enhance Acquisition and Speaking Compentence of BIPA Leaners at UNS Solo - Diahnisa, Tifany; Suyitno, Suyitno; Rakhmawati, Ani (Bina Nusantara University, 2023)
The aim the research was to describe the acquisition of words and the use of various conversational languages used by international students either in a classroom or in extra-curricular activities outside the classroom. Conversations and introductions to Indonesian culinary food were the hallmarks of teaching Indonesian to foreigners at Universitas Negeri Sebelas Maret, Solo. The rich traditions of Indonesian society were very attractive to foreign people. The Bahasa Indonesia bagi Penutur Asing (BIPA) learners arrived from different countries, such as Nigeria, Afghanistan, Palestine, Uzbekistan, and several other students from Arab nations. The research applied a qualitative descriptive research using case study method. Data were obtained from the observation of participants and nonparticipants, both activities inside and outside the classroom. The research reveals that the use of basic words, formed words, abbreviated words, and words or phrases of various slang is found. In various conversations, many words and phrases with a foreign language structure and the use of non-standard languages that do not correspond to the correct rules of Indonesian grammar are used. They have a tendency to use their mother tongue's pronunciation when expressing difficult words. Language acquisition at this stage can be an initial strategy for BIPA learners to be able to fight and survive in a native-speaking society.